2018
DOI: 10.1121/1.5027817
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic vaporization threshold of lipid-coated perfluoropentane droplets

Abstract: Phase shift droplets vaporizable by acoustic stimulation offer the advantages of producing microbubbles as contrast agents in situ as well as higher stability and the possibility of achieving smaller sizes. Here, the acoustic droplet vaporization (ADV) threshold of a suspension of droplets with a perfluoropentane (PFP) core (diameter 400-3000 nm) is acoustically measured as a function of the excitation frequency in a tubeless setup at room temperature. The changes in scattered responses-fundamental, sub-, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 55 publications
4
26
0
1
Order By: Relevance
“…Using larger micrometer-sized PFC droplets, an early report showed that the activation threshold decreased when the agents were exposed to US pulses of increased frequency (Kripfgans et al, 2004). A similar trend in PCCA activation thresholds was found when using smaller PFC-based nanodroplets (Aliabouzar et al, 2018;Sheeran et al, 2013;Sheeran et al, 2016), which agreed with our findings and what nucleation therapy predicts. Several studies have also demonstrated that PCCA activation thresholds are considerably reduced when using larger PCCAs (Kripfgans et al, 2004;Miles et al, 2016;Schad and Hynynen, 2010;Shpak et al, 2014), going from room to body temperatures (Schad and Hynynen, 2010;Williams et al, 2013), or by incorporating PFC compounds with lower boiling points during PCCA formulation (de Gracia Lux et al, 2017;Matsunaga et al, 2012;Sheeran et al, 2011).…”
Section: Figsupporting
confidence: 91%
See 1 more Smart Citation
“…Using larger micrometer-sized PFC droplets, an early report showed that the activation threshold decreased when the agents were exposed to US pulses of increased frequency (Kripfgans et al, 2004). A similar trend in PCCA activation thresholds was found when using smaller PFC-based nanodroplets (Aliabouzar et al, 2018;Sheeran et al, 2013;Sheeran et al, 2016), which agreed with our findings and what nucleation therapy predicts. Several studies have also demonstrated that PCCA activation thresholds are considerably reduced when using larger PCCAs (Kripfgans et al, 2004;Miles et al, 2016;Schad and Hynynen, 2010;Shpak et al, 2014), going from room to body temperatures (Schad and Hynynen, 2010;Williams et al, 2013), or by incorporating PFC compounds with lower boiling points during PCCA formulation (de Gracia Lux et al, 2017;Matsunaga et al, 2012;Sheeran et al, 2011).…”
Section: Figsupporting
confidence: 91%
“…In the presence of US wave energy, this nanodroplet vaporization process occurs beyond a critical peak negative pressure, which is called the vaporization or activation threshold. Importantly, the activation threshold depends on the properties of the nanodroplet PFC liquid core and phospholipid coating, ambient conditions, and US excitation parameters (Aliabouzar et al, 2018;Hoyt et al, 2016;Kripfgans et al, 2004;Martz et al, 2011;Sheeran et al, 2012;Shpak et al, 2014).…”
Section: Theorymentioning
confidence: 99%
“…The lung surfactant nanodrops formed in this study did not spontaneously vaporize at physiological temperature or at very low ultrasound MIs, but rather vaporized in a controllable manner at MIs suitable for diagnostic imaging and therapeutic applications. The implementation of the three different ultrasound systems operating at different transmit frequencies indicate that MI was a suitable parameter to control to initiate ADV, although prior literature has shown inconsistent effects of frequency and pressure on nanodrop ADV [27]. This is an important result illustrating the ability for lung surfactant nanodrops to be rapidly translated to the clinic.…”
Section: Resultsmentioning
confidence: 97%
“…Intermediate response resulting from the presence of the nanoemulsion near the liposomes is influencing drug release, possibly by enhanced energy transfer to the lipid bilayer that can deform or disrupt the bilayer. The phase transition of PFC from liquid to gas, which is in the range of 1 to 10 MPa (Aliabouzar et al, 2018), and the resulting expansion seems a plausible mechanism for the more efficient payload release. Thermal effects can be excluded since the maximum temperature increase upon HIFU exposure did not exceed 2 degrees (data not shown).…”
Section: Resultsmentioning
confidence: 99%